Efektivitas Konsentrat Papain Bubuk, Getah Pepaya Segar, dan Papain Komersial sebagai Koagulan dalam Pembuatan Dangke - Muh. Achyar Ardat; Zakiah Wulandari; Irma Isnafia Arief (Institut Pertanian Bogor, 2022)
Dangke is a milk-based dish in which the papain coagulates casein. This study aims to test the effectiveness of powdered papain concentrate, fresh papaya sap, and commercial papain as a coagulant agent in the dangke preparation with three additional levels of enzyme activity in each type of papain. The resulting dangke was tested physically, chemically, and organoleptically to determine the type of papain and the enzyme's activity level most effectively as a coagulant. The three enzyme activity levels used were 217.14, 434,29, and 651.44 AU/mg with a heating temperature of 100.16°C. The experiment used a randomized group design factorial pattern with three replications. Testing on the physical properties of the two types of papain showed results that did not differ significantly (P>0.05) for the whey weight but differed significantly for the yield. The results of the chemical properties test showed significantly different results (P<0.05) on the protein level. Based on hedonic quality tests, the dangke that is liked was chewy in texture, white in color, predominantly milky, has a distinctive dangke taste, and does not taste bitter. The hedonic quality on Anova test indicated a significantly different result (P<0.05) for all tested parameters. The best papain as a coagulant in dangke making was fresh sap papain and freeze-dried papain with the addition of the lowest level of enzyme activity, or level one. Keywords: coagulant, dangke, enzyme activity, organoleptic, papain